Melanocortin receptor agonist NDP-α-MSH improves cognitive deficits and microgliosis but not amyloidosis in advanced stages of AD progression in 5XFAD and 3xTg mice - Daini, Eleonora; Vandini, Eleonora; Bodria, Martina; Liao, Wenjie; Baraldi, Carlo; Secco, Valentina; Ottani, Alessandra; Zoli, Michele; Giuliani, Daniela; Vilella, Antonietta (Frontiers in Immunology, 2023)
Introduction Alzheimer’s disease (AD) is the most frequent cause of dementia and still lacks effective therapy. Clinical signs of AD include low levels of endogenous melanocortins (MCs) and previous studies have shown that treatment with MC analogs induces neuroprotection in the early stages of AD. Methods We investigated the neuroprotective role of MCs in two transgenic mouse models of severe AD using 5 and 7 month-old (mo) 5XFAD mice and 9 and 12 mo 3xTg mice. These mice were subjected to a chronic stimulation of MC receptors (MCRs) with MC analogue Nle4-D-Phe7-α-melanocyte stimulating hormone (NDP-α-MSH, 340 μg/kg, i.p.). Mouse behavior and ex-vivo histological and biochemical analyses were performed after 50 days of treatment. Results Our analysis demonstrated an improvement in cognitive abilities of AD mice at late stage of AD progression. We also showed that these protective effects are associated with decreased levels of hyperphosphorylated Tau but not with Aβ burden, that was unaffected in the hippocampus and in the cortex of AD mice. In addition, an age-dependent NDP effect on glial reactivity was observed only in 3xTg mice whereas a global downregulation of p38 mitogen-activated protein kinase was selectively observed in 7 mo 5XFAD and 14 mo 3xTg mice. Conclusion Our results suggest that MCR stimulation by NDP-α-MSH could represent a promising therapeutic strategy in managing cognitive decline also at late stage of AD, whereas the effects on neuroinflammation may be restricted to specific stages of AD progression.